European standard clinical practice recommendations for paediatric high-grade gliomas - Elwira Szychot; Géraldine Giraud; Darren Hargrave; Dannis van Vuurden; Jacques Grill; Veronica Biassoni; Maura Massimo; André O. Von Büren; Rejin Kebudi; Maria João Gil-da-Costa; Sophie Veldhuijzen van Zanten; Simon Bailey; et al. (EJC Paediatric Oncology)
Paediatric high-grade gliomas (pedHGGs) are highly invasive brain tumours accounting for approximately 15 % of all central nervous system (CNS) tumours in children and adolescents. The outcome for these tumours is generally poor with 5-year survival rates of less than 20 %. Despite improved biological insights into pedHGGs and the promise of more effective therapies, little progress has been made in the effective treatment and the outcome of these tumours over the last four decades. Much of the evidence for the use of chemotherapy in pedHGGs is extrapolated from adult data, and the evidence for its use in the paediatric population is still weak. This guideline was written by members of the SIOPE HGG Working Group as part of the European Standard Clinical Practice (ESCP) Project. The guideline aims to integrate available evidence-based and expert opinion-based information to assist healthcare professionals in the management of pedHGGs and in an attempt to provide equity in healthcare reflecting the varying resources of each European country.